Plasma Proteome Profiles of Stable CAD Patients Stratified According to Total Apo C‐III Levels. Issue 3 (7th August 2018) - Manfredi, Marcello; Chiariello, Carmela; Conte, Eleonora; Castagna, Annalisa; Robotti, Elisa; Gosetti, Fabio; Patrone, Mauro; Martinelli, Nicola; Bassi, Antonella; Cecconi, Daniela; Marengo, Emilio; Olivieri, Oliviero
Abstract : Purpose: The present research reports the study the of plasma proteome profile of stable coronary artery disease (CAD) patients characterized by different levels of total Apolipoprotein‐CIII (Apo C‐III), a prognostic marker for cardiovascular risk. Experimental design: Two subgroups of CAD patients ( n = 52) with divergent concentrations of total circulating Apo C‐III (≤ and ≥10 mg dL −1 ) are examined using a shotgun proteomic approach. Validation experiments are also performed with immunochemistry methods including both the patients affected by CAD ( n = 119) and the subjects without CAD (CAD‐free; n = 58). Results are analyzed by bioinformatics tools and multivariate statistics. Results: A total of 188 proteins are quantified among the patients. The fold change analysis and the partial least square discriminant analysis show a clear separation of the two groups. Lipoproteins (Apo C‐II and Apo E), retinol‐binding protein 4, and vitronectin are upregulated in patients with high Apo C‐III, while alpha‐1 antitrypsin is downregulated. Conclusions and clinical relevance: In this pilot study, the differential expression of plasma proteins related to different concentrations of Apo C‐III is defined, suggesting possible new players involved in the Apo C‐III‐associated process of arterial damage. Data are available via ProteomeXchange with identifier PXD005973.